Ireland in perspective : the art of Brian O'Doherty / Patrick Ireland - Moore McCann, Brenda (Trinity College (Dublin, Ireland). Department of History of Art and Architecture, 2002)
This dissertation set out to evaluate the contribution of an artist known by the double artistic persona, Brian O’Doherty/Patrick Ireland. It is the first critical analysis of the artist’s work over the past forty years. Taking as its starting point the pioneering role within the first generation of conceptual artists in New York during the late 1960s, it seeks to establish the nature of that contribution, then, and since then, and to place the oeuvre within its appropriate historical context. By so doing, in addition to providing the fullest account yet of one of conceptual art’s significant practitioners, it provides a greater understanding of the history of a relatively neglected area of contemporary art until recent times.
Keywords: History of Art and Architecture, Ph.D.; Ph.D. Trinity College Dublin